Pengaruh Kepemimpinan Transformasional, Kompetensi Kepuasan Kerja Terhadap Kinerja Guru Sekolah Menengah Umum - Marliana; Hanny Zahara Utami Harahap; Dhea Fithaloka; Ikhwanoor Khair; Marzuki; Effendi Sadly (Journal of Trends Economics and Accounting Research, 2023)
The objectives of this research are: (1) To determine the influence of transformational leadership on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. (2) To determine the effect of teacher competency on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. (3) To determine the effect of teacher job satisfaction on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. (4) To determine the influence of transformational leadership, competence and teacher job satisfaction on teacher performance at SMA Negeri 1 Tamiang Hulu Aceh Tamiang Regency simultaneously. This research was carried out at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. With a population of 40 people. The sample in the study was determined using a total sampling technique, so the number of samples was also 40 people. Data collection techniques use non-test methods, with questionnaire research instruments and library studies. Data analysis uses SPSS with descriptive analysis and regression analysis. The research results show that: (1) There is a positive and significant influence of the transformational leadership variable on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. (2) There is a positive and significant influence of the teacher competency variable on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency. (3) There is an influence of teacher job satisfaction on teacher performance at SMA Negeri 1 Tamiang Hulu Aceh Tamiang Regency. (4) There is an influence of transformational leadership, teacher competency, and job satisfaction on teacher performance at SMA Negeri 1 Tamiang Hulu, Aceh Tamiang Regency.